N,N-Dimethyl-p-toluidine, a Component in Dental Materials, Causes Hematologic Toxic and Carcinogenic Responses in Rodent Model Systems - Dunnik, June K. (Toxicol Pathol, 2013)
Because of the potential for exposure to N,N-dimethyl-p-toluidine (DMPT) in medical devices and the lack of toxicity and carcinogenicity information available in the literature, the National Toxicology Program conducted toxicity and carcinogenicity studies of DMPT in male and female F344/N rats and B6C3F1/N mice. In these studies, a treatment-related macrocytic regenerative anemia characterized by increased levels of methemoglobin and Heinz body formation developed within a few weeks of DMPT exposure in rats and mice. DMPT induced nasal cavity, splenic, and liver toxicity in rats and mice at 3 months and 2 years. DMPT carcinogenic effects were seen in the liver of male and female rats and mice, the nasal cavity of male and female rats, and the lung and forestomach of female mice. In rodents, DMPT is distributed to many of the sites where toxic and carcinogenic effects occurred. DMPT-induced oxidative damage at these target sites may be one mechanism for the treatment-related lesions. Methemoglobinemia, as seen in these DMPT studies, is caused by oxidation of the heme moiety, and this end point served as an early alert for other target organ toxicities and carcinogenic responses that followed with longer term exposure.